PERANAN REPRESENTASI BERBANTUAN SOFTWARE MAPLE PADA PEMBELAJARAN MATA KULIAH KALKULUS - Arie Candra Panjaitan (MES: Journal of Mathematics Education and Science, 2019)
Abstract. Computers are essential tools for teaching, learning, and doing mathematics. Computers can visualize or represent mathematical ideas, organize and analyze data, and calculate effectively and accurately. Computers can help students conduct investigations through representations in various fields of mathematics such as geometry, calculus, statistics, algebra, measurements, and numbers. This paper discusses the role of Maple assisted representation in calculus learning. Representation is very supportive in increasing students' understanding of mathematical relations and concepts. There are three main functions of representation, namely complementing, constraining, and constructing. Complementing function is to complete the process and complete the information. The constraining function is to help students experience difficulties in a representation. The constructing function is to support constructing a deeper understanding of a concept. Students can get a deeper understanding if difficulties with only one representation. Maple software is a facility that is very supportive in making representations in learning mathematics as in calculus learning. By using Maple we can do numerical and symbolic calculations and perform graphical representations well. Maple can also effectively determine limits, derivatives, integrals, and a series of other functions and capabilities. With this Maple software capability, we can use it to improve students' understanding of calculus courses.Keywords: Representation, Computers, Maple, Calculus